MEDAN MAKNA VERBA MENGAMBIL DALAM BAHASA DAYAK BANYADU? - Endang, Asteria; Hanye, Paternus; Susilo, Firman (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
The general problem this research is taken verb meaning field in Dayak Banyadu> language. The purpose of this research is to describe meaning component, meaning field, and semantic function of taken verb meaning field. The method in this research is descriptive method. The data in this research are words that contain taken verb meaning. The source of data is Dayak Banyadu> language.The technique in data collecting is conversation involving gathering technique and the research instrument are questions list, recording tape, data card, pictures, and photos. The result showed that taken verb in Dayak Banyadu> language is a two taken with tool and taken without tool. Keywords: verb, taken verb, meaning. Abstrak: Masalah umum penelitian ini adalah medan makna verba mengambil dalam Bahasa Dayak Banyadu>. Penelitian ini bertujuan mendeskripsikan komponen makna, jenis makna dan fungsi semantis verba mengambil. Metode dalam penelitian ini adalah metode deskriptif. Data penelitian ini adalah kata-kata yang mengandung makna verba mengambil. Sumber data adalah Bahasa Dayak Banyadu>. Teknik yang digunakan adalah teknik simak libat cakap dan alat pengumpulan data yaitu daftar pertanyaan, seperangkat perekam, kartu data, gambar dan foto. Hasilnya menunjukan bahwa verba mengambil dalam bahasa dayak Banyadu> ada dua yaitu mengambil menggunakan alat dan mengambil tanpa alat. Kata Kunci: verba, verba mengambil, makna